Systematic Literature Review: Lembar Kerja Peserta Didik Berbasis PMRI Pada Siswa Sekolah Menengah Pertama - Novitri Puspita Utami; Lucy Asri Purwasi; Rani Refianti (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
The development of Student Worksheets (LKPD) to improve mathematical problem-solving and conceptual understanding is an important effort in secondary mathematics education. Indonesian Realistic Mathematics Education (PMRI) provides a contextual learning approach that connects mathematical concepts with real-life situations. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines to analyze publication trends, material distribution, validity, practicality, and the effectiveness of PMRI-based LKPD for junior high school students. An initial search identified 28 articles, of which 15 were excluded for not meeting the inclusion criteria, resulting in 13 eligible studies for analysis. The findings indicate that PMRI-based LKPD consistently achieved very high validity (Aiken’s V = 0.80–0.92) and practicality (79.0%–98.6%). Geometry was the most frequently investigated topic (50%), reflecting its strong connection to visualization and real-world contexts. Overall, PMRI-based LKPD was found to be effective in enhancing students’ mathematical problem-solving, conceptual understanding, reasoning, critical thinking, and metacognitive skills. These findings support the integration of PMRI-based LKPD as an effective instructional resource for mathematics learning at the junior high school level.